Methyladenine as a regulator of biomolecular condensation - Arsiè, Roberto; Tartaglia, Gian G.; Vabulas, R. Martin (Frontiers in Molecular Biosciences, 2025)
Ribonucleotide modifications modulate RNA structure and stability, thereby influencing RNA turnover and a wide range of cellular functions. Recent studies have revealed that specific RNA modifications can also affect the formation, composition, and material properties of biomolecular condensates. This review explores how N1-methyladenine (m1A) and N6-methyladenine (m6A) contribute to RNA-driven phase transitions and the balance between adaptive granulation and pathological protein aggregation. m1A can act as a protective tag: by altering local RNA structure and RNA-protein interactions, it promotes the sequestration of selected transcripts into dynamic stress granules and facilitates the resumption of protein synthesis after stress. During chronic proteotoxicity, m1A helps prevent aberrant RNA-protein entanglement. However, when present on pathogenic repeat RNAs, m1A can recruit aggregation-prone proteins and exacerbate pathology. On the other hand, m6A functions as both a structural switch and a multivalent docking signal. Multiple m6A sites enhance the binding of cognate reader proteins to a transcript, thereby accelerating stress granule assembly. m6A modification has also been implicated in organizing nuclear condensates such as HSATIII lncRNA assemblies. We discuss mechanistic models that aim to reconcile the diverse roles of methyladenine, highlight current experimental challenges, and outline emerging approaches for addressing the remaining open questions.